2015
DOI: 10.1007/978-3-319-12961-7_9
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Phonology in Silent Reading: A Selective Review

Abstract: This chapter presents a selective review of evidence about how phonological representations are involved in silent reading. Knowledge of the mapping of orthography onto phonology appears to be important in skilled reading, and this knowledge is applied very early in the process of recognizing words in isolation. The same is true when one is reading sentences and texts, and the creation of a phonological representation of a text appears to play a critical role in guiding the movement of the eyes during reading.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…There seems to be a general consensus in the literature that phonological codes are integrated across saccades during reading (Clifton Jr., 2015; Cutter et al, 2015; Leinenger, 2014; Milledge & Blythe, 2019; Schotter et al, 2012). While this conclusion may often be accepted as a fact, there has been no attempt to make a statistical synthesis of all the available evidence supporting the existence of this effect.…”
Section: Present Studymentioning
confidence: 99%
“…There seems to be a general consensus in the literature that phonological codes are integrated across saccades during reading (Clifton Jr., 2015; Cutter et al, 2015; Leinenger, 2014; Milledge & Blythe, 2019; Schotter et al, 2012). While this conclusion may often be accepted as a fact, there has been no attempt to make a statistical synthesis of all the available evidence supporting the existence of this effect.…”
Section: Present Studymentioning
confidence: 99%
“…Proponents of this later role of phonological coding generally believe that the codes are used to integrate information across sentences, and/or to sustain information in working memory, since sound-based codes have been argued to be the most stable and retrievable short-term memory codes (Baddeley, 1979). Others have also suggested that it plays a role in restoring prosody and intonation to the memory trace (e.g., Bader, 1998; Breen & Clifton, 2011; 2013; Fodor, 2002; Hirotani, Frazier, Rayner, 2006, Kentner, 2012; for a recent review see Clifton, in press) and therefore, it has been argued that at least some component must come online post-lexically since there is no way to know the appropriate stress or intonation without a cursory processing of the sentence at several levels (e.g., Daneman & Newsome, 1992). However, there is evidence to suggest that prosodic information can influence first pass reading of a word (e.g., Ashby & Clifton, 2005; Breen & Clifton, 2011, 2013), suggesting that at least some aspects of prosody are being assigned during lexical access.…”
Section: Introductionmentioning
confidence: 99%
“…Upon recognizing the predominantly sad or joyful content of a poem, readers are likely to adjust their prosody—including the prosody of silent reading (for a review of the role of phonology in silent reading, see Clifton, 2015)—to the content of the poems. Since several studies report that the vocalizations of joy and sadness have their own acoustic profiles (Scherer, 1986; Banse and Scherer, 1996; Paulmann, 2006), readers may end up perceiving their own inner prosody along the lines of the phenomenological distinction in question.…”
Section: Discussion and Outlookmentioning
confidence: 99%